The revolution in Russia. To express sympathy with the Russian Revolutionists, a public meeting will be held… (SDF (Social Democratic Federation), 1906)
All text; black text on white paper Poster advertising meeting on 22 January, 1906, in the Memorial Hall, Farringdon Street, in support of the Russian revolution. Printed by the Twentieth Century Press, Ltd., Clerkenwell Green, London PO-1292